Exploring the potential roles of apelin, visfatin, and irisin in energy regulation in farm animals: an overview - Shokrollahi, Borhan; Jang, Sun-Sik; Lee, Hyun Jeong; Ahmad, Hafiz Ishfaq; Sesay, Abdul Rahman; Ghazikhani Shad, Ali; Morammazi, Salim; Abdelnour, Sameh A. (Frontiers in Veterinary Science, 2024)
Adipose tissue, both intricate and fundamental to physiological functions, comprises cell types, including adipocytes, pivotal in secreting bioactive peptides known as 'adipokines.' Apelin (APLN), Visfatin (VSFTN), and Irisin (IRSN) are novel adipokines involved in regulating energy, carbohydrate, protein, and lipid metabolism. APLN acts as an endogenous ligand for G-protein-coupled receptors, VSFTN is essential in nicotinamide adenine dinucleotide (NAD) biosynthesis, and IRSN is released from skeletal muscle and adipose tissues. Their influence spans various physiological domains, including insulin resistance and sensitivity, cardiovascular functions, angiogenesis, and reproductive systems. This review focuses on the potential roles of APLN, VSFTN, and IRSN in energy regulation mechanisms related to farm animal production. Despite accumulating evidence of their significance, comprehensive understanding is still emerging, with most studies based on model organisms. Thus, there's a pressing need for targeted research on farm animals. Addressing these knowledge gaps could pave the way for improved health strategies, reproductive efficiency, and productivity in farm animals. Future research should focus on understanding the multifaceted interactions of these adipokines and their implications for promoting sustainable and effective animal production.